Pengaruh Konten Kreatif dan Influencer Marketing terhadap Peningkatan Kunjungan Wisatawan di Kota Palembang - Maulinda Tri Yani; Sabeli Aliya (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2025)
The advancement of digital technology has significantly transformed the landscape of tourism promotion. Social media has now become a primary platform in shaping tourist perceptions and decision-making. Amid increasing competition among destinations, promotional strategies that rely on creative content and collaboration with influencers are considered more effective in building both visual and emotional appeal toward a tourism site. This study aims to analyze the influence of creative content and influencer marketing on the increase of tourist visits to Palembang City. The research employed a quantitative method with an associative-causal explanatory level. A total of 100 respondents were determined using the Slovin formula with a 10% margin of error, selected through simple random sampling. Data were collected through a Likert-scale questionnaire. The data analysis included validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination. The results show that creative content has a positive and significant effect on increasing tourist visits (t = 4.147; p = 0.000), as does influencer marketing (t = 5.714; p = 0.000). Simultaneously, both variables have a significant effect on the increase in tourist visits (F = 71.904; p = 0.000). The coefficient of determination (R²) of 0.597 indicates that 59.7% of the variation in the increase of tourist visits can be explained by these two variables, while the remaining 40.3% is influenced by other factors outside the model. These findings affirm that digital promotion strategies through creative content and influencer marketing significantly contribute to increasing tourist visits to Palembang City.